Growing with others: A longitudinal study of an evolving multi-sided disruptive platform - Alexander Lennart Schmidt; Neele Petzold; Norman Lahme-Hütig; Florian Tiemann (Creativity and Innovation Management, 2021)
Multi-sided platforms are becoming increasingly relevant in understanding industry changes. The literature has focused on the inception and growth of platforms, neglecting how entrants develop and grow disruptive platforms. To address this shortcoming, we study an entrant that was spun off from an established catalog retailer and is steering a multi-sided disruptive platform in the German fashion retail industry. We conduct a longitudinal study on how the entrant leverages the relationships with its multiple platform sides during 2014–2019 by analyzing secondary data using topic modeling and qualitative content analysis. We propose three levers: (1) “guarded inception,” which is the collaboration with a knowledgeable partner unaffected by disruption to quickly overcome the chicken-and-egg problem; (2) “activating force multipliers,” which is the strategic orchestration of complementors being contractually tied to the entrant and working to extend the entrant's value network. Enabled by these two levers, the entrant was (3) “building on others” to develop the platform along a disruptive path while circumventing internal limitations and external resistance. We contribute to the intersection of the literature strands on platform and disruptive innovation by showing how the entrant strategically leveraged its different platform sides over time to develop and grow a disruptive platform.
Keywords: 330; business model; disruptive innovation; platform; process; topic modeling